1963
DOI: 10.1177/004051756303300612
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Potentials of Vat Dyes and Their Relation to the Ease of Reduction and Tendering Behavior

Abstract: A. method. for ca~rying out potenttometric~itration of reduced vat dyes in aqueous alkaline solutions usmg a potassium ferricyanide solution as the oxidant is described The standard method is modified on the basis of certain assumptions, and the values of potentials~re~lculated and termed.".01aracteristic redox potentials." An account of the deter':lIn~tlOn of these charac~e\lslc redox potential values for a series of purified vat dyes IS given. The.characteristie redox potential values of vat dyes are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is also reported that a minimum pH of 12 to 14 is necessary for dyes to be reduced and solubilized completely, supporting the use of pH 13 in the present study. 55 Thus, the effects of pH on the PG cell can be explained by these facts. The performance of the cell is poor in acidic medium.…”
Section: Effects Of Variation Of the Alkalinity Of The Electrolyte Mementioning
confidence: 96%
“…It is also reported that a minimum pH of 12 to 14 is necessary for dyes to be reduced and solubilized completely, supporting the use of pH 13 in the present study. 55 Thus, the effects of pH on the PG cell can be explained by these facts. The performance of the cell is poor in acidic medium.…”
Section: Effects Of Variation Of the Alkalinity Of The Electrolyte Mementioning
confidence: 96%
“…In addition, there is no correlation between the reduction potential and the reduction rate ( Table 2). Such an account of the investigation on the ease of reduction of vat dyes is reported elsewhere [14]. However, it can be seen from the results in Table 1 that substitution of hydrogen by the more electronegative bromine or chlorine diminished the reduction rate, although this shifts the potential to more positive values [15].…”
Section: Electrochemical Reduction Of Different Single Vat Dyesmentioning
confidence: 65%
“…As the concentration of NaOH increase so does the pH of the solution. The QY being an acidic dye, is more susceptible to protonation of its sulphonic group at low pH leading to a positive charge on the dye molecules 33 . The dye protonation limits its tendency to donate electron leading to a lower current output of the cell, probable pathways have been suggested 34 …”
Section: Resultsmentioning
confidence: 99%
“…The QY being an acidic dye, is more susceptible to protonation of its sulphonic group at low pH leading to a positive charge on the dye molecules. 33 The dye protonation limits its tendency to donate electron leading to a lower current output of the cell, probable pathways have been suggested. 34 With the increase in concentration of NaOH, there is an increase in the alkalinity and a corresponding increase in pH of the solution.…”
Section: The Effect Of Variation Of Alkali (Sodium Hydroxide Naoh) Co...mentioning
confidence: 99%